Uma proposta para o ensino de noções de cálculo no Ensino Médio utilizando o Winplot - Santos, Cícero dos (2014)
It is notorious the importance of a good geometric vision in the study of certain contents, especially when they are related to Mathematics. In the exact sciences, among the contents that most demanding such vision is the Calculus. This important branch of mathematics is so feared by university students who became the object of study by some researchers. It is not for nothing that the Calculus is a major disciplines responsible for the high levels of disapprovals. Against this reality, this work propose the insertion of notions of Calculus in high school with an approach taken by Winplot software, because we believe that to relate the teaching learning to the use of a appropriate software, we can obtain a better comprehension and, therefore, a reduction in the indices of disapproval of this matter. In the intention to verify the e ectiveness of the proposal, we work with a class of 3rd grade of high school, between April and May 2014. Finally we analyzed this experience and found the e ectiveness of our proposal, with regard to the inclusion of notions Calculus in high school.